Rancang Bangun Aplikasi Pengujian Usability Berbasis Web - Zulfidiana, Zulfidiana; Yunardi, Dalila Husna; Mutiawani, Viska (Department of Informatics, Universitas Syiah Kuala, 2023)
Usability is one factor that influences software design success during the software testing process. Usability testing is used to evaluate whether the software meets user needs or not. Usability testing is usually carried out using a certain questionnaire method, but the distribution and measurement of the results are carried out separately. This makes the researchers spend more time testing the application. Therefore, this study provides a solution by designing and building web-based applications to measure the usability of a software design or product with the SUS, UMUX, and UMUX-lite questionnaires. The development method used in this study is Rapid Application Development (RAD) with the stages of the process starting with problem identification, literature study, needs planning, RAD design workshops, implementation, and report writing. The application was built using the Laravel framework and the database using MySQL. The main features of the online questionnaire application were the creation of a questionnaire and the analysis of the results of the questionnaire. The functionality of the application was tested by using the Black Box testing method. Then the developed application was also utilized in usability testing using the SUS, UMUX, and UMUX-lite questionnaires. The results of application usability testing using the SUS, UMUX, and UMUX-Lite methods obtained a final score of 88; 91,28, and 82,05 where all these values mean the application can be accepted and used. Keywords: Usability Testing, Rapid Application Development, SUS, UMUX, UMUX-Lite